ECONOMETRIC SOFTWARE - FREE VS. PAID SOLUTIONS - Nicolae-Marius JULA (Challenges of the Knowledge Society)
Using software in econometric analysis empower the researches to find the answer to the problems faster than ever. The use of commercial software is very wide-spread, but the costs are always a barrier for a lot of researchers. Using free alternatives like R combines the power processing with affordability. We analyze in this paper some aspects related to main differences between commercial econometric software and free alternatives.